1989
DOI: 10.1007/bf00314327
|View full text |Cite
|
Sign up to set email alerts
|

The cerebral localization of neuropsychological impairment in Alzheimer's disease: a SPECT study

Abstract: Twenty-three patients with a clinical diagnosis of Alzheimer's disease were examined with a set of neuropsychological tests and with 99mTc-hexamethyl-propyleneamineoxime (HMPAO) single photon emission computed tomography (SPECT). Correlations between test results and indices of regional HMPAO distribution were analysed by multidimensional scaling (MDS). Test results covaried positively with relative HMPAO uptake of frontal, inferior parietal and superior temporal regions but not, or in a negative way, with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

1990
1990
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 49 publications
2
18
0
1
Order By: Relevance
“…Thus, story-recall and word-learning scores were significantly correlated with activity in the right anterior and posterior cingulate cortex, respectively; though not part of our initial hypothesis, these correlations are not surprising as activations of the right or bilateral cingulate cortex are frequently observed in verbal episodic memory tasks (Grasby et al, 1993;Petrides et al, 1995;Schacter et al, 1996;Tulving et al, 1996). Word learning was also correlated with activity in the right inferior frontal gyrus (with a peak in BA 44 with SPM), in accordance with previous data (Goldenberg et al, 1989;McGeer et al, 1990;Waldemar et al, 1994). Activation of the right prefrontal cortex during word recall has been frequently reported both in healthy subjects (Squire et al, 1992;Shallice et al, 1994; for review, see Nyberg et al, 1996) and in Alzheimer's disease , and these findings have been incorporated into the framework of the hemispheric encoding/retrieval asymmetry (HERA) model which attributes a preferential role to the right prefrontal cortex in the retrieval of episodic material, regardless of its verbal or visuospatial nature (Tulving et al, 1994a).…”
Section: Episodic Memorysupporting
confidence: 77%
See 2 more Smart Citations
“…Thus, story-recall and word-learning scores were significantly correlated with activity in the right anterior and posterior cingulate cortex, respectively; though not part of our initial hypothesis, these correlations are not surprising as activations of the right or bilateral cingulate cortex are frequently observed in verbal episodic memory tasks (Grasby et al, 1993;Petrides et al, 1995;Schacter et al, 1996;Tulving et al, 1996). Word learning was also correlated with activity in the right inferior frontal gyrus (with a peak in BA 44 with SPM), in accordance with previous data (Goldenberg et al, 1989;McGeer et al, 1990;Waldemar et al, 1994). Activation of the right prefrontal cortex during word recall has been frequently reported both in healthy subjects (Squire et al, 1992;Shallice et al, 1994; for review, see Nyberg et al, 1996) and in Alzheimer's disease , and these findings have been incorporated into the framework of the hemispheric encoding/retrieval asymmetry (HERA) model which attributes a preferential role to the right prefrontal cortex in the retrieval of episodic material, regardless of its verbal or visuospatial nature (Tulving et al, 1994a).…”
Section: Episodic Memorysupporting
confidence: 77%
“…Regarding the latter, the almost complete lack of significant correlations with the activity in limbic structures (the posterior cingulate cortex apart) agrees with comparable studies in Alzheimer's disease (Goldenberg et al, 1989;McGeer et al, 1990;O'Brien et al, 1992;Waldemar et al, 1994;Ishii et al, 1996), as well as with PET activation studies with this task, whether in healthy subjects (for review, see Fletcher et al, 1997) or in Alzheimer's disease patients . Furthermore, these dissociations would be compatible with Schacter's model (Schacter et al, 1996), according to which the limbic system is preferentially involved in conscious but effortless recollection, and the prefrontal cortex in the process of controlled retrieval; for example, recalling a story is a more natural task (limbic system) than recalling a series of unrelated words, which probably demands greater organizational activity (prefrontal cortex).…”
Section: Figsupporting
confidence: 71%
See 1 more Smart Citation
“…Studies of brain-behavior relationships in AD patients may be useful for determining the cortical localization of soluble cognitive functions such as semantic memory [22]. However, the results of previous studies using single-photon emission computed tomography (SPECT) or positron emission tomography (PET) are highly unconvincing and conflicting [23][24][25][26][27][28][29][30][31][32][33]. A blood flow or metabolic abnormality in the frontal, parietal or temporal lobes of either side was reportedly correlated with semantic memory test scores.…”
mentioning
confidence: 75%
“…Repeatedly, studies demonstrated temporoparietal hypometabolism and reduced temporoparietal blood flow to be the typical metabolic abnormality associated with AD [15][16][17][18][19]. However, other studies also reported a heterogeneous pattern of SPECT findings in patients with mild AD [20,21], and FDG-PET and SPECT were thus considered to be too ambiguous to be used in routine diagnosis [10,22].…”
Section: Introductionmentioning
confidence: 99%